Paraneoplastic cerebellar degeneration: initial presentation of occult breast cancer - FİLİZOĞLU, NUH; KESİM, SELİN; ENGÜR, CEREN ÖZGE; ÖNEŞ, TUNÇ; ÖZGÜVEN, SALİH; ERDİL, TANJU YUSUF (My University, 2020)
Aim/Introduction: Paraneoplastic cerebellar degeneration (PCD) is a rare type of paraneoplastic syndrome characterized by the progressive onset of cerebellar dysfunction as a result of immune-mediated response against neoplasm rather than metastasis. We present a case of occult breast cancer who had PCD at initial presentation with diffuse cerebellar uptake depicted on the FDG PET/ CT scan. Six months after the treatment, a follow-up FDG PET/CT scan revealed complete resolution of the cerebellar hypermetabolism. Materials and Methods: FDG PET/CT was performed to A 64-year-old female patient presented with complaints of progressive dysarthria, ataxia, nystagmus, headache and gait disturbance. Results: FDG PET/CT showed diffuse and intensely increased uptake in both cerebellar hemispheres and vermis (A). FDG PET/CT images also depicted moderate hypermetabolic lymph node in the right axillary region; however, no hypermetabolic foci was detected in breast tissues (A). Histopathology of the right axillary lymph node revealed metastasis of breast cancer. Based on these findings, the diagnosis of paraneoplastic cerebellar degeneration associated with occult breast cancer was made and treatment with doxorubicindocetaxel-trastuzumab-pertuzumab was initiated. After four cycles of chemotherapy, follow-up FDG PET/CT showed complete regression of cerebellar hypermetabolism (B). Conclusion: PCD is a rare central nervous system disorder that is triggered by an immune system response to a neoplasm. PCD affects 1-3 % of all cancer patients, and it occurs typically in patients with cancer of the ovary, uterus, breast cancer, small-cell carcinoma of the lung and Hodgkin lymphoma. Patients typically develop subacute cerebellar ataxia, dysarthria, diplopia, and vertigo, which often precede the detection of the primary tumor. PCD is characterized by extensive loss of Purkinje cells and the presence of highly specific antineuronal antibodies in the serum and cerebrospinal fluid. Proteins expressed by tumors induce the production of onconeural antibodies leading to a T-cell mediated destruction of Purkinje cells in the cerebellum. The treatment of the underlying malignancyis considered the optimal treatment for PCD. FDG PET/CT is crucial in the early detection of the unknown primary tumors. Most of the recently published studies emphasizing the potential of FDG PET/CT in the assessment of the functional neurologic consequences of the disease in the brain as well as changes that follow after therapeutic interventions. To the best of our knowledge, this is the first case in the literature that uses FDG PET / CT to assess the current state of occult breast cancer with PCD and subsequently following up the disease